Institutional Multilingualism in NGOs: Amnesty International’s Strategic Understanding of Multilingualism - Tesseur, Wine (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2014)
Institutional multilingualism is most often associated with large intergovernmental institutions such as the European Union and the United Nations. Institutional multilingualism in non-governmental organisations (NGOs), however, has remained invisible to a large extent. Like international governmental organisations (IGOs), NGOs operate across linguistic borders. This raises the question whether NGOs use language and translation in the same way as IGOs. The present article takes Amnesty International as a case study, and explores what institutional multilingualism means for this organisation, how it is reflected in its language policy, and how it is put into practice. By gaining insight into the particular case of Amnesty International, this article aims to make a contribution to institutional translation studies.